2017
DOI: 10.1002/anie.201706487
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[7]uril as a Supramolecular Artificial Enzyme for Diels–Alder Reactions

Abstract: The ability to mimic the activity of natural enzymes using supramolecular constructs (artificial enzymes) is a vibrant scientific research field. Herein, we demonstrate that cucurbit[7]uril (CB[7]) can catalyse Diels-Alder reactions for a number of substituted and unreactive N-allyl-2-furfurylamines under biomimetic conditions, without the need for protecting groups, yielding powerful synthons in previously unreported mild conditions. CB[7] rearranges the substrate in a highly reactive conformation and shields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 43 publications
1
120
0
Order By: Relevance
“…Endo preference increases also in the presence of the macrocycle (endo/exo ratio 90 : 10 to 96 : 4 and 97 : 3 for CB [8]-bound tryptophane 92 a and abrine 92 b, respectively). [137] We [138,139] and Scherman [139] showed that CB [7] and CB [8] catalyze the intramolecular Diels-Alder cycloaddition of Nallyl-2-furfurylamines 93 (see Scheme 14) with rate enhancements greater than 10 3 for guests 93 b-93 e and CB [7]. The authors show convincing evidence that a ternary complex between the amino acid, the pyridine moiety of guest 90 and CB [8] is formed, with copper bound to both units, and the dienophile portion of guest 90 left outside the macrocycle near the rim and available for reaction with cyclopentadiene (see Figure 11).…”
Section: Guest Release and Capture Controlled By Ancillary Reactionsmentioning
confidence: 99%
“…Endo preference increases also in the presence of the macrocycle (endo/exo ratio 90 : 10 to 96 : 4 and 97 : 3 for CB [8]-bound tryptophane 92 a and abrine 92 b, respectively). [137] We [138,139] and Scherman [139] showed that CB [7] and CB [8] catalyze the intramolecular Diels-Alder cycloaddition of Nallyl-2-furfurylamines 93 (see Scheme 14) with rate enhancements greater than 10 3 for guests 93 b-93 e and CB [7]. The authors show convincing evidence that a ternary complex between the amino acid, the pyridine moiety of guest 90 and CB [8] is formed, with copper bound to both units, and the dienophile portion of guest 90 left outside the macrocycle near the rim and available for reaction with cyclopentadiene (see Figure 11).…”
Section: Guest Release and Capture Controlled By Ancillary Reactionsmentioning
confidence: 99%
“…Cucurbiturils are a series of supramolecular macrocyclic hosts with n glycoluril bridged by 2n methylenes, yielding cucurbituril series (CB [5,6,7,8,10,13,14,15]). CB [5][6][7][8][9][10] (except for CB [13][14][15]) share a common pumpkin-shaped structure with a large hydrophobic cavity and two negatively charged portals.…”
Section: Synthesis Of Cucurbiturilsmentioning
confidence: 99%
“…Cucurbiturils are a series of supramolecular macrocyclic hosts with n glycoluril bridged by 2n methylenes, yielding cucurbituril series (CB [5,6,7,8,10,13,14,15]). CB [5][6][7][8][9][10] (except for CB [13][14][15]) share a common pumpkin-shaped structure with a large hydrophobic cavity and two negatively charged portals. [26][27][28][29] Crystal structures indicates that the four biocompatible CB[n]s, such CB, [5] CB, [6] CB [7] and CB [8] have the same height of 9.1 Å and diverse outer diameters ranging from 13.1 Å -17.5 Å .According to the sizes of the cavities, the smaller cucurbituril of CB [5] can complex with some metal cations and gas molecules.…”
Section: Synthesis Of Cucurbiturilsmentioning
confidence: 99%
See 2 more Smart Citations